To determine who solved the equation correctly, let's start with the given equation and solve for \(y\).
The original equation is:
\[ 11x - 8y = -48 \]
We will isolate \(y\):
- First, subtract \(11x\) from both sides:
\[ -8y = -11x - 48 \]
- Next, divide each term by -8:
\[ y = \frac{11}{8}x + 6 \]
Now, let's compare this result to the work provided by Bob, Bill, and Bud:
-
Bob's solution:
- \(y = 7.375\) (This is incorrect as it does not represent the general solution for \(y\).)
-
Bill's solution:
- \(y = 118x + 6\) (This is incorrect due to the wrong coefficient for \(x\).)
-
Bud's solution:
- \(y = -11x + 6\) (This is incorrect because he incorrectly managed the signs and coefficients.)
Since none of them arrived at the correct solution, the correct response is:
None of them are correct.